The derivation of urban design principles in Malay-Islamic town of Kuala Terengganu - Abdul Latip, Nurul Syala; Harun, Nor Zalina; Abdullah, Alias; Ibrahim, Mansor (Malaysian Institute Of Planners, 2020)
Islam took root in the Malay Sultanate kingdom when trade flourished through the Straits of Malacca and the South China Sea. Islamic teaching was accepted by the locals and Islam became the country’s official religion. Islam has been assimilated in the way of life of the Malays, including the physical built environment of its cities. However, after colonisation, many of the Malay town structure had changed tremendously following the western planning. Remnants of the Malay-Islamic state footprint can still be traced in the town of Kuala Terengganu. This paper aims to establish the urban design principles influenced by the Islamic values which are embedded in and characterised in Kuala Terengganu. Employing a qualitative method, secondary and primary data (observation using photography) were collected. Content analysis were conducted on the observation data, archival documents, historical literatures and morphological study on Kuala Terengganu Town and triangulated with the literature on principles gathered from the characteristic of Islamic cities. The findings revealed that Kuala Terengganu has similar characteristics to other Islamic cities however it is translated in the local context. The comparison revealed fifteen Urban Design principles related to the Malay-Islamic Town of Kuala Terengganu that are well-assimilated and embedded within the local culture, geography and climate for the reference of future city planners.